Perception of the results obtained with the practice of mountain bike (Research, Society and Development, 2022)
The present study aimed to verify the perception of the results obtained for adhering to the practice of mountain biking. This is a crosssectional, descriptive study. The sample included 60 mountain bike practitioners with a mean age of 36.05 ± 11.14 years, 46 males and 14 females. The volunteers answered a structured form containing questions related to the study’s objectives. Descriptive analysis was used to characterize the sample. Categorical variables were displayed in the form of absolute and relative frequency. It was evidenced that from the total of 106 answers, 40.57% indicated physical conditioning as the main goal for the practice, 12.26% weight loss, and 10.38% muscle strength increase. Other factors reported by the study participants included muscle definition (7.55%), competition (5.66%), and muscle hypertrophy (4.72%).  18.87% of the answers corresponded to "other" goals in addition to those mentioned above, including aspects such as leisure, health promotion, and commuting. According to the perception of the study participants, considering the totality of the answers regarding the objectives, 83.96% noticed an improvement in the practice of mountain biking. It is concluded that the main objective for the practice of mountain biking reported by the study participants was physical conditioning. Most of them perceived improvement according to the objectives for joining the practice of the sport.